Unveiling the Neuroprotective Potential of Date Palm (Phoenix dactylifera): A Systematic Review - Syed Mohammed Basheeruddin Asdaq; Abdulaziz Ali Almutiri; Abdullah Alenzi; Maheen Shaikh; Mujeeb Ahmed Shaik; Sultan Alshehri; Syed Imam Rabbani (Pharmaceuticals)
Background: Neurodegenerative diseases primarily afflict the elderly and are characterized by a progressive loss of neurons. Oxidative stress is intricately linked to the advancement of these conditions. This study focuses on Phoenix dactylifera (P. dactylifera; Family: Arecaceae), commonly known as “Ajwa,” a globally cultivated herbal plant renowned for its potent antioxidant properties and reported neuroprotective effects in pharmacological studies. Method: This comprehensive systematic review delves into the antioxidant properties of plant extracts and their phytochemical components, with a particular emphasis on P. dactylifera and its potential neuroprotective benefits. Preferred reporting items for systemic reviews and meta-analysis (PRISMA) were employed to review the articles. Results: The study includes 269 articles published in the literature and 17 were selected after qualitative analysis. The growing body of research underscores the critical role of polyphenolic compounds found in P. dactylifera, which significantly contribute to its neuroprotective effects through antioxidant mechanisms. Despite emerging insights into the antioxidant actions of P. dactylifera, further investigation is essential to fully elucidate the specific pathways through which it confers neuroprotection. Conclusions: Like many other plant-based supplements, P. dactylifera’s antioxidant effects are likely mediated by synergistic interactions among its diverse bioactive compounds, rather than by any single constituent alone. Therefore, additional preclinical and clinical studies are necessary to explore P. dactylifera’s therapeutic potential comprehensively, especially in terms of its targeted antioxidant activities aimed at mitigating neurodegenerative processes. Such research holds promise for advancing our understanding and potentially harnessing the therapeutic benefits of P. dactylifera in neuroprotection.